Pengaruh Literasi Keuangan, Penggunaan SIA, Inklusi Keuangan, dan Digital Payment Terhadap Kinerja UMKM di Sragen (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of financial literacy, accounting information system usage, financial inclusion, and digital payment on the performance of MSMEs in Sragen Regency. A quantitative method was employed through a survey involving 75 culinary MSME actors in Sragen. Data were collected using questionnaires and analyzed using multiple linear regression. The results indicate that financial literacy, accounting information systems, financial inclusion, and digital payment simultaneously have a significant effect on MSME performance. Partially, financial literacy and digital payment were found to have a positive and significant effect. Meanwhile, financial inclusion and the use of accounting information systems did not have a significant impact on MSME performance. These findings highlight the importance of entrepreneurs’ financial management capabilities and the adoption of technology to improve operational efficiency. This study provides practical insights for MSME actors, local governments, and financial institutions in formulating empowerment strategies based on digitalization and financial literacy.